Microplastics and Antibiotics in Aquatic Environments: A Review of Their Interactions and Ecotoxicological Implications - Tang, Kuok Ho Daniel (Tropical Aquatic and Soil Pollution, 2024)
Microplastics and antibiotics are two significant emerging pollutants found together in water bodies, raising concerns about their mutual effects. This review delves into how microplastics and antibiotics interact in aqueous environments and the ecotoxicological implications of such interactions, particularly the bioavailability of antibiotics and the prevalence of antibiotic-resistance genes. It outlines that antibiotics attach to microplastics primarily through hydrophobic, hydrogen-bonding, and electrostatic interactions. Other bonds, comprising halogen bonding, cation−π interaction, and negative charge-assisted hydrogen bonds, may also be involved to better explain antibiotic adsorption patterns. The adsorption of antibiotics to microplastics often follows the pseudo-second-order kinetic model and in some instances, the pseudo-first-order kinetic model. The common adsorption isotherms governing this interaction are the linear and Freundlich models. Microplastics may increase the biodegradation of adsorbed antibiotics due to the presence of antibiotic-degrading bacteria in the biofilms. They could also hamper direct photodegradation but facilitate indirect photodegradation of adsorbed antibiotics. However, their photodegradative effect remains inconclusive. Microplastics and antibiotics exhibit significant toxicity to algae, while their effects on fish and daphnia are less noticeable, suggesting that their combination does not pose an immediate threat to the well-being and proliferation of larger aquatic organisms. In some instances, microplastics reduce the deleterious effects of antibiotics on aquatic life. Microplastics serve as catalysts for gene transfer, enhancing the propagation of antibiotic-resistance genes in these ecosystems. This review underscores the importance of understanding the regulatory mechanisms of microplastics on antibiotic-resistance gene diversity, particularly at the gene expression level.